Oxycodone versus morphine for analgesia after laparoscopic endometriosis resection - Lijun Niu; Lihong Chen; Yanhua Luo; Wenkao Huang; Yunsheng Li (BMC Anesthesiology, 2021)
Abstract Background The objective of this study was to compare the analgesic potency of oxycodone versus morphine after laparoscopic deep infiltrating endometriosis resection. Methods Fifty patients undergoing laparoscopic deep infiltrating endometriosis resection were randomized to receive oxycodone or morphine intravenous-PCA after surgery. The primary outcome was opioid consumption during the 24 h after surgery. Secondary outcomes included time to first request for analgesia, the number of bolus, pain, sedation, nausea, vomiting, respiratory depression, and bradycardia. The prominent pain that caused patients to press the analgesic device was also recorded. Results Oxycodone consumption (14.42 ± 2.83) was less than morphine consumption (20.14 ± 3.83). Compared with the morphine group, the total number of bolus (78 vs 123) was less and the average time to first request for analgesia (97.27 ± 59.79 vs 142.17 ± 51) was longer in the oxycodone group. The incidence of nausea was higher in the morphine group than in the oxycodone group at 0–2 h (45.45% vs 17.19%), 2–4 h (50% vs 17.19%),12–24 h (40.91% vs 13.04%) and 0–24 h (39.17% vs 19.13%). The overall incidence of vomiting was higher in the morphine group (27.27% vs 13.92%). There was no difference in visual analogue scale score, the incidence of respiratory depression, and bradycardia between groups. Of the three types of pain that prompted patients to request analgesia, the incidence of visceral pain was highest (59.9%, P < 0.01). Conclusion Oxycodone was more potent than morphine for analgesia after laparoscopic endometriosis resection, and oxycodone has fewer side effects than morphine. Name of the registry: Chinese Clinical Trial Registry Trial registration number: ChiCTR1900021870 URL of trial registry record: http://www.chictr.org.cn/edit.aspx?pid=35799&htm=4 Date of registration: 2019/3/13 0:00:00